Resolution of the Quantum Multiverse and Quantum Consciousness Relationship through Everything Everywhere All at Once - Erol, Alkım; Erol, Mustafa (Cinémas, 2025)
This study investigates how the film Everything Everywhere All at Once (EEAAO) proposes a form of cinematic thinking on the relationship between the quantum multiverse and quantum consciousness through its cinematic language. Quantum theory introduces a number of conceptually challenging ideas, such as the Many-Worlds Interpretation (MWI), quantization, the principle of superposition, and quantum probability, which continue to invite philosophical speculation and scientific inquiry. Similarly, quantum consciousness remains an unsettled topic in modern science that deserves more interest and consideration. Acknowledging the contested and speculative nature of these concepts, this study attempts to analyze the film in an experimental and heuristic way. This work focuses on revealing how EEAAO cinematically thinks on the specified relationship. This objective is reached through a close reading analysis of the film following a structural model on the narrative of cinematic language, and through concentrating on analyzing simultaneously operating and interacting microstructural and macrostructural elements. The analysis concludes that EEAAO offers a distinctive philosophical contribution precisely because it employs cinematic language rather than verbal language to communicate its cinematic thinking on the relationship between the quantum multiverse and quantum consciousness.